Immunohistochemical expression of vascular endothelial growth factor-C in renal cell carcinoma subtypes: Ekspresi imunohistokimia faktor pertumbuhan endotel vaskular-C pada subtipe karsinoma sel ginjal - Haider, Omar F.; Al-Nuaimy, Wahda M.T. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Vascular Endothelial Growth Factor-C is a glycoprotein encoded by the Vascular Endothelial Growth Factor-C gene, initially produced as an inactive precursor and activated through proteolytic processing. It belongs to the vascular endothelial growth factor family and plays a crucial role in angiogenesis (blood vessel formation) and lymphangiogenesis. Objectives of the study: To evaluate the immunohistochemical expression of Vascular Endothelial Growth Factor-C in renal cell carcinoma subtypes. To assess its association with some clinicopathological parameters. Methods: In this prospective and retrospective case series study, fifty cases of surgically excised kidney biopsies were included. The blocks of the cases were collected from Al-Jumhory teaching hospital and some private laboratories in Mosul city in a period from October 2023 to July 2024. Section slides from the blocks were stained by Vascular Endothelial Growth Factor-C. Interpretation of the slides and statistical analysis has been done. Results: The age of 50 renal cell carcinoma cases ranged from 21 to 77 years (mean± standard deviation= 55.6±13.5) with 56% of them ≥ 55 years, male to female ratio 2:3, 78% of cases were of clear cell renal cell carcinoma, regarding tumor grading 44% grade II, 34% with positive lymphovascular invasion, 48% were tumor stage T1. Among the fifty cases, 56% were with high level of expression of VEGF-C with 59% of them < 55 years old, 63% males, 56% were of clear cell renal cell carcinoma, 82.4% of them with positive lymphovascular invasion show high expression of VEGF-C. Conclusion: High VEGF-C expression was predominantly observed in cases with higher tumor grades (III and IV), also there is a high expression with advanced stages (T3 and T4), and lymphovascular invasion, suggesting that VEGF-C may serve as an important parameter for more aggressive and invasive forms of RCC. Highlight : High VEGF-C expression significantly correlates with advanced tumor grade (III–IV) and stage (T3–T4), indicating aggressive cancer behavior. VEGF-C shows strong association with lymphovascular invasion, suggesting its role in tumor dissemination and poor prognosis. VEGF-C expression may serve as a potential biomarker for identifying invasive renal cell carcinoma and guiding targeted therapy. Keywords : Renal Cell Carcinoma, Vascular Endothelial Growth Factor-C, Clear Cell Carcinoma, Tumor Grade, Lymphovascular Invasion